Meningkatkan Kemampuan Passing dalam Bermain Sepak Bola melalui Pendekatan Discovery Learning - Manalu, Nimrot; Fauzi, Abrar; Sary, Putri Wulan; Sihotang, Alwi Prima; Zahra, Hafizhah (JURNAL KELUARGA SEHAT SEJAHTERA, 2025)
In the context of passing orientation, this method encourages players to explore various passing techniques, understand game situations, and improve creativity and decision-making on the field. This study uses a descriptive qualitative method used to describe the phenomenon in depth based on data collected from observations, interviews, and documentation (Sugiyono, 2019). Data collection in this study was collected using the literature review technique, which is a research method carried out by examining various relevant literature sources. The results of this study, namely In football, passing orientation based on Discovery Learning emphasizes players' understanding of passing techniques and tactics through activities that allow them to learn independently and collaboratively.